Superficial Temporal Recipient Vessels for Craniofacial Microvascular Free-Flaps. Issue 6 (22nd September 2022) - Awwad, Lina; Obed, Doha; Vogt, Peter M.; Kaltenborn, Alexander; Koenneker, Soeren
Abstract : The selection of recipient vessels for microvascular free-flaps is critical in craniofacial reconstruction. Especially the suitability of the superficial temporal vessels is questioned conflictingly in the literature. The aim of this study was to share our experience with microvascular craniofacial free-flap reconstruction and to evaluate a set of factors that are related to the recipient vessels and to determine how these factors influence flap survival. We conducted a retrospective analysis of 39 free-flaps for craniofacial reconstruction that were performed from 2006 until 2020 and evaluated the indication for microvascular reconstruction, recipient vessels, various factors related to the recipient vessels and complications. The most utilized recipient artery was the facial artery, selected in 20 patients followed by the superficial temporal artery selected in 12 patients. The most commonly used recipient vein was the facial vein used in 16 patients, followed by the superficial temporal vein selected in 10 patients and the external jugular vein in 6 patients. Total flap necrosis occurred in one patient. There was no statistically significant association between the selected recipient vessels and patient comorbidities, major and minor complications, revision of anastomosis or flap loss. The results of our study have demonstrated that the superficial temporal artery and vein show similar results when used for face and scalp reconstruction. Considering their technical and aesthetic advantages they may be the first choice recipient vessels in established free-flap treatment algorithms for craniofacial reconstruction.